Bremsstrahlung of electrons and yield of neutrons from thick converters, passing of gamma-radiation and neutrons through biological shielding - Deiev, O.S.; Bochek, G.L.; Dubina, V.N.; Kiprich, S.K.; Vasilyev, G.P.; Yalovenko, V.I.; Ovchinnik, V.D.; Shulika, M.Y. (Вопросы атомной науки и техники, 2019)
In GEANT4 spectral-angular distributions of the bremsstrahlung of medium-energy electrons from amorphous targets of diﬀerent thickness and atomic charge were calculated. The total yield of gamma quanta in the forward hemisphere and at large scattering angles were determined depending on the converter thickness. The diﬀerence in the characteristics of gamma radiation for thin and thick targets was shown. The neutron yield is calculated due to photonuclear reactions for various converters. Numerical estimates of the radiation spectra after passing through the biological shielding for neutron and bremsstrahlung were carried out. У GEANT4 розраховано спектрально-кутові розподіли гальмівного гамма випромінювання електронів середніх енергій з аморфних мішеней-конверторів різної товщини і атомного заряду. Визначено повний вихід гамма-квантів у передню півсферу і під великими кутами розсіювання в залежності від товщини конвертора. Показано відмінність характеристик гамма-випромінювання для тонких і товстих мішеней. Проведено розрахунок виходу нейтронів за рахунок фотоядерних реакцій для різних конверторів. Проведено чисельні оцінки спектрів випромінювання після проходження біологічного захисту окремо для нейтронного і гальмівного випромінювань. В GEANT4 рассчитаны спектрально-угловые распределения тормозного гамма-излучения электронов средних энергий из аморфных мишеней-конверторов различной толщины и атомного заряда. Определен полный выход гамма-квантов в переднюю полусферу и под большими углами рассеяния в зависимости от толщины конвертора. Показано различие характеристик гамма- излучения для тонких и толстых мишеней. Проведен расчет выхода нейтронов за счет фотоядерных реакций для различных конверторов. Проведены численные оценки спектров излучения после прохождения биологической защиты отдельно для нейтронного и тормозного излучений.